Educational antimicrobial stewardship programs in medical schools: a scoping review. Issue 11 (13th November 2021) - Augie, Bashar M.; Miot, Jacqui; van Zyl, Robyn L.; McInerney, Patricia A.
ABSTRACT: Objective: The objective of this scoping review was to identify the available evidence on antimicrobial stewardship programs for teaching medical students about rational antimicrobial use, including the content taught and the method of instruction used. Introduction: Antibiotics are a precious resource whose discovery have saved millions of lives. They are used extensively in surgical procedures, cancer chemotherapy, and in the treatment of infectious diseases. However, the development of antimicrobial resistance and the slow rate of discovery of new agents with novel mechanisms of actions represent a threat to modern medicine. Inclusion criteria: This scoping review considered papers that described medical school curricula that focused on the teaching and learning of the prescription of antimicrobial medication. Studies that described this concept in the curricula of other health profession students, such as nursing, pharmacy, or dentistry students, were excluded. Methods: The JBI three-step process was followed and conducted by two reviewers. The scoping review followed an a priori published protocol. Eight databases were searched for both published and unpublished literature and gray literature. Only studies published in English from 1996 onwards were included. Full texts of selected citations were assessed against the inclusion criteria by two independent reviewers. Data were independently extracted by two reviewers. Disagreements were resolved through discussion, and the need for a third reviewer was not required. Data extraction was undertaken using a modified charting table developed for the review objectives. The findings are presented using the narrative synthesis. Results: Thirteen studies were included in the review, with most of the papers originating from the United States of America and Europe, with one from developing countries. Didactic lectures and web-based distance learning were the most common modes of instruction used in the included papers. Six of the included papers presented the outcomes of their interventions; different methods of assessment were used to evaluate students, which included baseline and post-instruction assessment or a series of short exams. Some of the concepts in the teaching material included the use of antimicrobial agents, prevention of antimicrobial resistance, antimicrobial stewardship, and infection prevention control. The programs (ranging from 75 minutes to 100 hours) were implemented from second to fourth year of study. Conclusions: A wide range of interventions were used to teach the principles of antimicrobial stewardship to medical students. There is a need to further evaluate these programs through follow-up of students after graduation to determine whether the skills learned are retained.